Desenvolvimento e implantação da distribuição alternada como frequência de entrega do serviço postal - Simmer, Diogo Medeiros (2020)
The objective of this paper is to present the implementation of alternate distribution in postal services in order to optimize performance and reduce operating costs in the provision of mandatory universal service. For this, a systematic literature review on the universal postal service was carried out, its current scenario was verified, basing it with conceptual and empirical research, in order, finally, to implement the new distribution methodology. We used a methodological approach to action research, which allowed us to raise the existing operational dysfunctions and the unsatisfactory performances of operations critical to the business. Through this implementation, based on the change in the frequency of delivery of postal services, it is possible to verify whether the results of the alternation in distribution can be a possible solution for the decline in the volume of postal items. Subsequently, an analysis and validation of the improvements implemented were carried out. The results obtained showed that the implementation of this alternation in the distribution of correspondence improved the performance in the distribution and reduced the organization's operating costs. Add to this that this methodology can also be applied to the logistics sector as a solution to recurring problems in distribution and result in possible operational optimization. The technical product was delivered to the researched institution